2021
DOI: 10.1038/s41598-021-01410-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing for coronavirus (SARS-CoV-2) based on gene co-expression network analysis

Abstract: Severe acute respiratory syndrome (SARS) is a highly contagious viral respiratory illness. This illness is spurred on by a coronavirus known as SARS-associated coronavirus (SARS-CoV). SARS was first detected in Asia in late February 2003. The genome of this virus is very similar to the SARS-CoV-2. Therefore, the study of SARS-CoV disease and the identification of effective drugs to treat this disease can be new clues for the treatment of SARS-Cov-2. This study aimed to discover novel potential drugs for SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 110 publications
(78 reference statements)
0
14
0
Order By: Relevance
“… Title Datasets used Repurposed Drugs Evaluation Criteria Tools used Ref. 1 Designing a Network Proximity-Based Drug Repurposing Strategy for COVID-19 BioGRID Network proximity/ Network Diffusion Cytoscape, VarElect tool [169] 2 Network medicine framework for identifying drug-repurposing opportunities for COVID-19 13 Datasets, DrugBank, STRING 989 Drugs, 77 Validated in VeroE6 Cells, 76/77 validated in Human Cells Network proximity, network diffusion, Network AI Experimental, Ensembl algorithmic prediction [176] 3 Drug repurposing for coronavirus (SARS-CoV-2) based on gene co-expression network analysis DGIDb, gene co-expression, DrugBank 5 Drugs Gene enrichment analysis for Genes and miRNA Node degree and centralities [195] 4 Network-based repurposing identifies anti-alarmins as drug candidates to control severe lung inflammation in COVID-19 Uniprot, STRING, CMap, LINCS, GEO Gene expression profiling CMap ranking [184] 5 Integrative In Silico Investigation Reveals the Host-Virus Interactions in Repurposed Drugs Against SARS-CoV-2 STITCH, KEGG, BioGRID, PubChem, IID, Enrichment analysis, Molecular docking DAVID, GOplot, AutoDock Vina, Cytoscape, Ligplot+ [196] 6 Discovery of Potential Therapeutic Drugs for COVID-19 Through Logistic Matrix Factorization with Kernel Diffusion 4 Drugs 5-fold cross validations, AUC, AUPRs, recall, similarity diffusion Molecular docking [197] 7 HeTDR: Drug repositioning based on heterogeneous networks and text mining Mesh, DrugBank, PubMed 10 Drugs AUPR, AUROC, F1-measure [198] 8 ...…”
Section: Network Based Studies For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“… Title Datasets used Repurposed Drugs Evaluation Criteria Tools used Ref. 1 Designing a Network Proximity-Based Drug Repurposing Strategy for COVID-19 BioGRID Network proximity/ Network Diffusion Cytoscape, VarElect tool [169] 2 Network medicine framework for identifying drug-repurposing opportunities for COVID-19 13 Datasets, DrugBank, STRING 989 Drugs, 77 Validated in VeroE6 Cells, 76/77 validated in Human Cells Network proximity, network diffusion, Network AI Experimental, Ensembl algorithmic prediction [176] 3 Drug repurposing for coronavirus (SARS-CoV-2) based on gene co-expression network analysis DGIDb, gene co-expression, DrugBank 5 Drugs Gene enrichment analysis for Genes and miRNA Node degree and centralities [195] 4 Network-based repurposing identifies anti-alarmins as drug candidates to control severe lung inflammation in COVID-19 Uniprot, STRING, CMap, LINCS, GEO Gene expression profiling CMap ranking [184] 5 Integrative In Silico Investigation Reveals the Host-Virus Interactions in Repurposed Drugs Against SARS-CoV-2 STITCH, KEGG, BioGRID, PubChem, IID, Enrichment analysis, Molecular docking DAVID, GOplot, AutoDock Vina, Cytoscape, Ligplot+ [196] 6 Discovery of Potential Therapeutic Drugs for COVID-19 Through Logistic Matrix Factorization with Kernel Diffusion 4 Drugs 5-fold cross validations, AUC, AUPRs, recall, similarity diffusion Molecular docking [197] 7 HeTDR: Drug repositioning based on heterogeneous networks and text mining Mesh, DrugBank, PubMed 10 Drugs AUPR, AUROC, F1-measure [198] 8 ...…”
Section: Network Based Studies For Covid-19mentioning
confidence: 99%
“…There are multiple significant studies utilizing this approach to repurpose the drugs in Covid-19 and other diseases. Once recent Covid-19 based drug repurposing study is done in [195] where gene co-expression-based network for 1441 genes was constructed and analysis was performed. The analysis resulted in two significant gene co-expression network modules and then data related to miRNAs and transcription factors targeting co-expressed modules’ genes were gathered from reputable databases led to the establishment of two subnetworks consisted of transcription factors and miRNAs.…”
Section: Network Based Studies For Covid-19mentioning
confidence: 99%
“…The outbreak of SARS-CoV-2 spawned multiple analyses where the goal was to select substances that can be useful in COVID-19 treatment. Most of the studies apply a drug repurposing strategy that identifies new therapeutics from already approved substances, since de novo identification of drugs is a costly and lengthy process [28] . In one of the research studies, it was found that emodin, omipalisib, and tipifarnib can serve as inhibitors of RdRp [26] .…”
Section: Introductionmentioning
confidence: 99%
“…Another docking study revealed that the drugs cytarabin, raltitrexed, tenofovir, cidofovir, lamivudine and fludarabine are potent binders of the spike protein [30] . In other research, rather than finding specific protein targets, the authors analyzed gene-interaction networks and found several potential drugs including fluorouracil, cisplatin, sirolimus, cyclophosphamide, and methyldopa [28] . Several other drugs such as chloroquine, hydroxychloroquine, remdesivir, galidesivir and others were also considered for potential treatment of COVID-19 patients [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Drug repositioning is also referred to as drug repurposing, drug therapeutic, drug recycling, and drug reprofiling 13 , 14 . There are usually three kinds of methods for drug repurposing, including experimental biological methods, computational methods, and mixed methods 10 , 15 , 16 . Computational methods can be referred to as molecular docking, network mapping, signature matching, genetic association, and retrospective clinical analysis 13 , 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%